19-6(5x-4)=-5

Simple and best practice solution for 19-6(5x-4)=-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 19-6(5x-4)=-5 equation:


Simplifying
19 + -6(5x + -4) = -5

Reorder the terms:
19 + -6(-4 + 5x) = -5
19 + (-4 * -6 + 5x * -6) = -5
19 + (24 + -30x) = -5

Combine like terms: 19 + 24 = 43
43 + -30x = -5

Solving
43 + -30x = -5

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-43' to each side of the equation.
43 + -43 + -30x = -5 + -43

Combine like terms: 43 + -43 = 0
0 + -30x = -5 + -43
-30x = -5 + -43

Combine like terms: -5 + -43 = -48
-30x = -48

Divide each side by '-30'.
x = 1.6

Simplifying
x = 1.6

See similar equations:

| 5=.86x | | x^4+21x^2=0 | | -2.6x=42.64 | | 9x+5=9(x-2) | | 6(2x-2)=-8(x+4) | | 3x-9=3(x-4) | | 4xsquared-3x+1=0 | | 4.1y=8.2 | | 2/3x-1/7=4/5 | | 2/3m-1/7=4/5 | | 4y-2=2y+4 | | 2c-14=4c | | a(5x-6)=-45x+54 | | -9x-12x=84 | | .20x+.82=-.13x+3.34 | | 7+3(x+2)=4(x-7) | | -6b=-36 | | 7x-13+5x=2x-11 | | .2x+.82=-.13x+3.34 | | (36/(x+3))-(15(x+9))=1 | | (8/x)-1=8/(x-1) | | 36-91d-78-5d+3+6d= | | 9+m=26 | | n/12=10 | | sqrt(x-2)=9 | | .06/12= | | x=-5x^2-2x+16 | | 2r+2=5x-11 | | Abs(5x-1)-1=6 | | sqrt(x^2+9)-3=2 | | m+5m-8m+2= | | 4b-5b=5 |

Equations solver categories